METHOD OF INCREASING COMBINE HARVESTER MAINTAINABILITY - Yury A. Tsarev; Sergey V. Filobok; Olga O. Barannikova (Advanced Engineering Research, 2012)
The solution to the problem connected with increasing the service reliability of the combine harvesters at the expense of cutting time on the delivery of spare parts to the field is offered.